2002
DOI: 10.1074/jbc.m200129200
|View full text |Cite
|
Sign up to set email alerts
|

p38 and Activating Transcription Factor-2 Involvement in Osteoblast Osmotic Response to Elevated Extracellular Glucose

Abstract: Poorly controlled or untreated type I diabetes mellitus is characterized by hyperglycemia and is associated with decreased bone mass and osteoporosis. We have demonstrated that osteoblasts are sensitive to hyperglycemia-associated osmotic stress and respond to elevated extracellular glucose or mannitol by increasing c-jun and collagen I expression. To determine whether MAPKs are involved in this response, MC3T3-E1 osteoblasts were treated with 16.5 mM glucose, mannitol, or contrast dye for 1 h. Immunoblotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 75 publications
2
44
0
Order By: Relevance
“…However, several metabolic disturbances postulated to affect bone formation negatively are characteristic of 9-week-old male ZDF rats-including deficiency in leptin signaling, insulin resistance, and hyperglycemia (McCarthy et al 1999, Zayzafoon et al 2002, Tamasi et al 2003. Evidence has accumulated to suggest that in type-2 diabetes, bone formation and/or turnover are impaired due to glucose metabolic and hormonal disturbances that might modulate osteoblastic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several metabolic disturbances postulated to affect bone formation negatively are characteristic of 9-week-old male ZDF rats-including deficiency in leptin signaling, insulin resistance, and hyperglycemia (McCarthy et al 1999, Zayzafoon et al 2002, Tamasi et al 2003. Evidence has accumulated to suggest that in type-2 diabetes, bone formation and/or turnover are impaired due to glucose metabolic and hormonal disturbances that might modulate osteoblastic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that type-2 diabetic osteoporosis is associated with depression of osteoblastic activities, resulting in a decrease in bone formation (Inaba et al 1999, Takizawa et al 2003. In in vitro studies, elevated extracellular glucose has been shown to change osteoblast phenotype by inhibiting osteocalcin expression (Inaba et al 1995, Terada et al 1998, Zayzafoon et al 2002. Irreversible advanced glycosylation end-products (AGEs) are generated by even sporadic elevations in blood glucose and appear to act through specific receptors (RAGEs) to increase the levels of inflammatory cytokines (tumor necrosis factor-α and interleukin-6), which have been shown to negatively affect the balance of bone formation/resorption.…”
Section: Discussionmentioning
confidence: 99%
“…32 In the case of osmotic stress, p38 and JNK phosphorylation is first detected 5 min after the insult is applied 30,33 and their activity reaches a maximum level 20-60 min later. 30,34 Does activating p38 during antephase delay entry into mitosis? The answer here is clearly yes: activating p38 in antephase cells with anisomycin, 22 or exogenous α and β, but not γ, isoforms of p38, 20 delays progression into mitosis (see also ref.…”
Section: P38 and The G 2 /M Transitionmentioning
confidence: 99%
“…Transcription of the FN gene is accomplished by p38 mitogen-activated protein kinase (MAPK) activation and cyclic AMP response element (CRE)/ CCAAT site-dependent phosphorylation of the activating transcription factor 2 (ATF2; refs. 28,29). Additional transcription factors involved in FN gene transcription are CRE-binding protein (CREB) and early growth response-1 (EGR-1; refs.…”
Section: Introductionmentioning
confidence: 99%